Effects of Sapindoside-containing concentrate on productive performance and rumen fermentation in heifers - Jiao Yang; Huang Wenming; Guo Haiming; Ye Jun'an (浙江大学学报. 农业与生命科学版, 2015)
Sapindoside is a type of triterpenoid saponins and is extracted from Sapindus mukorossi pericarp by anhydrous ethanol. Previous studies reported that Sapindoside can regulate rumen fermentation in vitro, but whether it is effective in vivo is still unknown. Thus, the objective of the study is to investigate the effects of Sapindoside-containing concentrate on productive performance, nutrient digestion, rumen fermentation and plasma biochemical indexes in 25-28 month-old heifers.Sixteen Chinese Holstein heifers, 144 days left to give birth, were used in a 95 d trial (7 d for adaptation). The animals were assigned to two treatments: basal diet with or without 0.15% Sapindoside (powder of 80% triterpenoid saponins) in concentrate. The adding level was based on our previous experiment in vitro. At the last week of the trial, a total of 12 heifers, six from each treatment, were randomly selected, and subjected to a digestion trial by index method with acid insoluble ash as index. The samples of blood and rumen fluids were collected on the day before the last day of the trial. Body size indexes were measured every month and body mass was calculated by formula.Results showed that body height, body length, heart girth and estimated body mass had an increase trend (P> 0.05) in Sapindoside-containing group, and the estimated average daily gain of the whole period was increased by 31% compared with the control (P=0.05). Apparent total tract digestibility of dry matter (DM, P<0.01), organic matter (OM, P<0.01), crude protein (CP, P<0.01), ether extract (EE, P>0.05), neutral detergent fiber (NDF, P< 0.05), acid detergent fiber (ADF, P< 0.01) and crude ash (P< 0.01) were greater in Sapindoside-containing group compared with the control. Protozoa counts, concentration of ammonia-nitrogen, total volatile fatty acids as well as acetate and propionate were not affected by Sapindoside-containing concentrate (P> 0.05). However, butyrate concentration, acetate to propionate ratio and estimated methane production decreased in Sapindoside-containing group (P< 0.05). Moreover, no difference was found in blood biochemical indexes, including total protein, albumin, globulin, urea nitrogen, glucose, total cholesterol, triglyceride, non-esterified fatty acid, β-hydroxybutyrate, total bilirubin, creatinine, glutamic-pyruvic transaminase, glutamic-oxalacetic transaminase, alkaline phosphatase and superoxide dismutase between two groups (P>0.05).In summary, feeding Sapindoside-containing concentrate presents a trend to improve the productive performance of 25-28 month-old heifers. Meanwhile, further studies are required to explore the Sapindoside's adding level and the long-term effects of Sapindoside on heifers.